COMPETENCY APPROACH IN TEACHING CHEMISTRY - Umarov, Saidanvar (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
This article presents the effectiveness of the use of the competence-based approach in teaching chemistry. The main goal of applying the competence-based approach in education is aimed at creating a mechanism for applying theoretical knowledge in practice, ensuring the process of personal formation, adaptation to new conditions, the development of self-defense, self-education, self-improvement and other features that contribute to the development of a perfect personality in the following areas.